POTENTIAL ANALGESIC AND ANTI-INFLAMMATORY EFFECT OF CUMINUM CYMINUM AND BORAGO OFFICINALIS IN RATS AND MICE - GIHAN F ASAAD; ALAA Q REDAI; ALAA O HAKAMI; FATIMAH Y GHAZWANI; YOUSRA NOMIER; SAEED ALSHAHRANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Our research aimed to study the potential therapeutic effect of Cuminum cyminum and Borago officinalis seed oil against inflammation induced by carrageenan as well as its central and peripheral analgesic effect. Methods: The anti-inflammatory effect was determined by measuring the edema rate and inhibition rate using Plethysmometer. Writhing test and hot plate test were used to determine the peripheral and central analgesic effect, respectively. Key Findings: Significant anti-inflammatory effects were witnessed for all the drugs at different dose levels in the results. Substantial analgesic effect against both peripheral and central pain induction was also incurred on administration of all doses of C. cyminum and B. officinalis seed oil. Conclusion: The C. cyminum and B. officinalis seed oil has potent anti-inflammatory and analgesic effects.